Psychological status of medical staff dedicated to nucleic acid collection in COVID-19 epidemic during closed-loop management: A cross-sectional study - Sun, Mingzhu; Li, Xiaowei; Yao, Jie; Huang, Xi; Kang, Yujuan; Li, Zixuan (Frontiers in Public Health, 2023)
Background: To investigate the depression, anxiety and somnipathy situation occurred in the nucleic acid collection staff during the closed-loop management period of COVID-19. And try to understand the influencing factors of related psychological status. Methods:By applying convenient sampling method, 1,014 nucleic acid collection staff who engage in closed-loop management of RT-PCR collection from seven grade-A tertiary hospitals in Shaanxi Province were investigated by using online questionnaire survey from March 25 to April 18, 2022 .The questionnaires,including the 12-iten self-made questionnaire survey of basic demographic information, 9-item patiens health questionnaire depression scale (PHQ-9), 7-item generalized anxiety disorder scale (GAD-7) and pittsburgh sleep quality index (PSQI) to investigate the prevalence of depression, anxiety and somnipathy in respondents and analyze disparate data. Results:The positive rate of depression, anxiety and sleep disorder of 1,014 nucleic acid collectors under closed-loop management were 33.5%, 27.2% and 50.1% respectively. Depression was signifificantly positively correlated with anxiety and sleep(P < 0.05) .The scores of depression scale were positively correlated with the age and the fear for infection (r=0.106, 0.218, both P < 0.05); The scores of anxiety scale were also positively correlated with the age and the fear for infection (r=0.124, 0.225, both P < 0.05); The length of service,collection time and the degree of worry about infection and was positively correlated with the score of sleep scale (r=0.077, 0.074,0.195,both P < 0.05); Education level had a signifificant negative association with PHQ-9、GAD-7 and PSQI (r=-0.167, -0.172 ,both P < 0.05). Binary logistic regression analysis showed that age, technical title, education level, collection time, collection frequency, collection location, fear for infection and external environment were important influencing factors of depression, anxiety and sleep disorders. Conclusion:The depression, anxiety and somnipathy situation in nucleic acid collection staff were in high level. Therefore, when carrying out nucleic acid collection mission, it is necessary to optimize the collection location, control each time of collection mission, replace the collection staff in time, and pay close attention to the psychological state of the collection staff. These are of great benefits to the psychological state of nucleic acid collectors.